1998
DOI: 10.1111/1467-9868.00152
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Variance In Nonparametric Regression—What is a Reasonable Choice?

Abstract: The exact mean-squared error (MSE) of estimators of the variance in nonparametric regression based on quadratic forms is investigated. In particular, two classes of estimators are compared: Hall, Kay and Titterington's optimal difference-based estimators and a class of ordinary difference-based estimators which generalize methods proposed by Rice and Gasser, Sroka and Jennen-Steinmetz. For small sample sizes the MSE of the ®rst estimator is essentially increased by the magnitude of the integrated ®rst two squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(134 citation statements)
references
References 21 publications
6
125
0
3
Order By: Relevance
“…, d r for the calculation of the pseudo residuals. As pointed out by Dette, Munk and Wagner (1998), the sequence (d 0 , . .…”
Section: Testing For Homoscedasticitymentioning
confidence: 93%
“…, d r for the calculation of the pseudo residuals. As pointed out by Dette, Munk and Wagner (1998), the sequence (d 0 , . .…”
Section: Testing For Homoscedasticitymentioning
confidence: 93%
“…where l denotes the difference operator applied l subsequent times (Rice, 1984;Hall et al, 1990;Seifert et al, 1993;Dette et al, 1998). This estimator was introduced in Vrugt et al (2005) and was shown to work well for daily and hourly discharge data.…”
Section: Case Studies: Hydrologic Modelingmentioning
confidence: 99%
“…If the errors e i were independent and identically distributed, 185 then g(t) ≡ σ 2 e = e i 2 , the variance of e i . In this case we can apply difference-based variance estimators and there is a huge literature on the estimation of σ 2 e ; see Rice (1984), and Dette et al (1998), among others. In our setting, however, due to the dependence, the difference-based approach is generally invalid.…”
Section: ·6 Estimation Of Variance Functionsmentioning
confidence: 99%